SISTAT: ferramenta computacional como proposta para o ensino da estatística - Saraiva, José Carlos Coelho (2016)
The statistical is part of the mathematical language, which is often seen as difficult to understand, having also own symbology which requires prior presentation to be fully understood. This way, the reading and the information understanding provided by many ways of communication are impaired when there is no approach and or appropriate work with basic education students. In our practice inside or outside of the classroom, we have noticed lack of technological resources and teaching methodologies and alternative learning directed to teaching Statistics to assist the teacher in the development and expansion of specific theme content. Then we guess that our survey and development of our own educational material is justified as a possible contribution to the improvement of teaching and learning providing the teacher and students new ways to dealing with statistical knowledge involving technologies as microcomputers which fits very well in this gap, through possibility to software developing with specific educational goals. Our Educational material called Systat which its development is the main goal of our survey it’s a computational tool with scope to support teaching process of descriptive statistics contents which students will be able to have a better understanding of concepts, statistical technics and information analysis. Students will understand how calculation were carried out without excessive spending time with a complex and repetitive calculations.